Environmental significance of lichens and biodeterioration - (:unkn) unknown (Springer Singapore, 2019)
This chapter underlines the environmental values of lichens, an important part of biodiversity on Earth, and at the same time addresses the subject of biodeterioration in detail. Diversity and sociology of lichens, ecological factors effective on growth and distribution of the lichens, bioindicative and biomonitoring roles of lichens in the air pollution and also roles of lichens in ecological events such as erosion prevention, succession and soil formation in nature were mentioned under the brief headings. Information was given on the occurrence of biological deterioration "biodeterioration", both physical and chemical properties and functions of the event and the organisms causing the biodeterioration. Biological deterioration occurring in the presence of living organisms such as lichens, fungi and mosses known as eroding stone surfaces, while qualifying as damaging in the case of historical monuments and works of art, also represents a fundamental process of the biosphere. The literature on biodeterioration of stone monuments and artiefacts, especially by lichen species and other organisms, and also the protective methods in this area have been reviewed. This compilation is intended to provide information on the importance of lichens for the environment as much as it is for biodeterioration and is thought to be a guide for the establishment of management and conservation strategies today. © Springer Nature Singapore Pte Ltd. 2020. All Rights reserved.
Keywords: Biodeteriogen; Biodeterioration; Biological weathering; Lichen diversity; Monument; Stonework